Teores de nutrientes, produtividade e qualidade pós-colheita do maracujá-amarelo submetido a adubação orgânica e silicatada - Silva, Juliana Pereira da (2018)
The production of yellow passion fruit is already well established in the Brazilian Northeast, however, some cultural practices such as organic fertilization in the crop need to be elucidated, as well as the increase of productivity with the use of some mineral compounds such as silicon. In view of the above, the objective of this research was to evaluate the nutrition and post-harvest quality of two varieties of yellow passion fruit, in two subsequent crops, as a function of two sources of organic fertilization, without and with application of silicon in the soil-climatic conditions of Agreste Pernambucano. The experimental design was a randomized complete block design with four replications, consisting of 12 treatments, evaluated in two consecutive seasons. Two varieties of yellow passion fruit 'Redondo amarillo' and 'BRS Sol do Cerrado' were used. The fertilizations were with tanned bovine manure (10L per pit) and tanned chicken bed (2L per pit). The silicate fertilization was with potassium silicate via soil (40ml of solution per plant). The experimental unit consisted of two plants. The leaf contents (N, P, K and Si), as well as the nitrogen, phosphorus and potassium contents, carbon and organic matter in the soil, as well as productivity, were evaluated. The fruits were evaluated for mass of the fresh matter (fruit, bark and pulp), fruit length and diameter, firmness, bark color (L, a, b, C and H), pulp color (C and H), soluble solids , titratable acidity and pulp yield. The data were evaluated through analysis of variance, and means were compared by the Tukey or F test. The interactions of organic fertilizers, especially bovine manure, with potassium silicate increased the nutrient content, both in soil and leaves, as well as productivity of yellow passion fruit. The quality of the fruits of plants submitted to organic fertilization presents physical characteristics of greater acceptance for the consumer market of yellow passion fruit.